Developing Project-Based Learning-Based eBook "Critical and Creative Reading" to Improve Students' Critical Thinking Skills - Riswanda Himawan; Pujiati Suyata; Ari Kusmiatun (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2024)
This study aims to examine the feasibility and effectiveness of the development of electronic-book-based Critical and creative reading project to improve students ' critical thinking skills. This study was developed based on the Research and Development (R&D) model by Brog and Gall. The stages conducted in this study were (1) needs analysis, (2) planning, (3) development, (4) product validity, (5) revision, (6) response test, (7) revision, and (8) final product development. The product validity was assessed by two experts in teaching materials and graphs as the validators. The result of the validity assessment was then processed using the five-scale formula. The revision was done to meet the validators’ suggestions. Response test was conducted with students of the Indonesian Language Education Department of Universitas Ahmad Dahlan. The test results were processed using the AIKEN V formula. A revision was then made to meet students’ suggestions obtained from the test. At last, a trial was carried out to measure the effectiveness of the product in order to become the guideline to develop the final product.The research findings were as follows: (1) the lecturers and students in learning critical and creative reading in higher education expected teaching materials that were easily accessible, electronic, and collaborated with one of the learning models so that they were able to measure the success rate of the critical and creative reading process; (2) product development was carried out through the activities of designing materials, models and evaluations that were developed in a product, as well as designing electronic books in accordance with the results of the needs analysis; (3) the appropriateness test results by the material experts obtained 3.40 in the good category and the layout expert scored 4.65 with a very good category. The results of the response test for students after being calculated with the Aiken V formula obtained a score of 0.85 – 1.00 with a very good category. The results of the experimental test showed that the posttests of the control and experimental classes obtained results of 0.001, which showed <0.05, so H0 was rejected. Students' critical thinking skills after the treatment were significantly different. Therefore, the teaching material developed was effectively used to improve students' critical thinking skills.